Determinan Kejadian Berat Bayi Lahir Rendah - Iva Inpresari; Wiwik Eko Pertiwi (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Riskesdas (2018), shows that the proportion of LBW in Indonesia is 6.2% and has not yet reached the 2019 National target (6.9%). The number of LBW in Serang District Health Office (DHO) during 2018 reached 662 cases, and babies with LBW ranks first among the causes of infant death in Serang District, as many 84 cases (35%) of babies died due to LBW. Jawilan Public Health Centre ranks first (7%) and then Petir Public Health Centre as many 6% in the LBW incidence rate in Serang District. Objective: This study aims to determine the factors associated with the incidence of Low Birth Weight (LBW).Method: This study uses a case control design. The study was conducted in March to June 2019 with a sample of 142 people consisting of 71 case samples and 71 control samples. Case samples in this study were mothers who gave birth to babies with birth weights less than 2500 mg (2.5 kg) and control samples were mothers who gave birth to babies of normal weight.Results and Discussion: The results showed that 22.5% of ANC frequencies were not good, 33.8% of upper arm circumference/LILA were not good, 41.5% of pregnancy distances were at risk and 18.3% were preeclampsia. The results showed that there was a significant relationship between ANC frequency and size of LILA with LBW (pv = 0.003, pv = 0.008), there was no relationship between pregnancy distance, preeclampsia with LBW (pv = 0.089, pv = 0.129).Conclusion: there was no correlation between pregnancy distance, preeclampsia with LBW. Key word: ANC frequency; Low Birth Weight; Size of LILA